Art and the Power to Save: William Ricketts and Mary Packer Harris in the Atomic Age - Handasyde, Kerrie (Journal for the Academic Study of Religion, 2022)
When churches protested the testing of atomic weapons, the rhetoric of power reigned. William Ricketts and Mary Packer Harris responded with religiously-informed artworks that protested humanity’s violence and subverted conventional representations of divine power. Harris, a Quaker, saw Christ crucified in every tree lost to Adelaide’s urban development and each atomic test. Ricketts, potter and founder of the William Ricketts Sanctuary, Mount Dandenong, produced sculptures protesting society’s violence toward First Nations peoples and the environment. While Harris remained resolutely Christian in her art and protest, Ricketts modelled Christ-like figures on himself. With clay-sculpted arms outstretched, he was Aboriginal Australia’s suffering saviour. Focusing on the years following atomic testing at Maralinga, this article examines the relationship between Harris and Ricketts and their representations of Christ in places of suffering that were ‘new’ to mid-century Australian consciousness, each hoping their art (if not Jesus) had the power to save.